Performance of Kaolin Clay on hot-mix asphalt properties - Putra Jaya, Ramadhansyah; M. K. I., Mohd Satar; M. H., Rafsanjani; N., Che Mat; Mohd Rosli, Hainin; Md. Maniruzzaman, A. Aziz; Mohd Ezree, Abdullah; Dewi Sri, Jayanti (IOP Publishing, 2018)
Kaolin clay is a waste product with numerous applications in construction. This study explored the addition effect of kaolin clay on the properties of hot-mix asphalt. Four replacement levels of kaolin clay were considered by weight of binder, i.e., 2%, 4%, 6%, and 8%. The performance of kaolin clay on the hot-mix asphalt was evaluated through a Marshall stability and flow test, including stiffness, density, voids in total mix, and voids in filled with asphalt. Test results showed that kaolin clay can be satisfactorily used as filler replacement material to increase the asphalt mixture properties. Generally, asphaltic concrete with 2% kaolin clay replacement level exhibits excellent performance with good stability and stiffness.